Planejamento e desenvolvimento urbano: o desafio da estratégia do desenvolvimento orientado ao transporte no município de Goiânia - Prado, Luciano Gomes do (2024)
Efficient urban planning is crucial to promoting sustainable economic development in municipalities, especially in developing countries. In this area, the principles of Transportation Oriented Development (TOD) are emerging as an urban planning tool that seeks to place land use and occupation rules, the road system and urban mobility at the center of urban development. Likewise, the master plan, as the main regulatory instrument responsible for establishing the basic rules for land use and occupation, is an essential mechanism for guiding urban development. In this regard, economist Albert O. Hirschman, as a great advocate of economic planning, believes that the State plays an essential role in promoting development, through public investments as an instrument to boost economic growth. Thus, planning is closely linked to economic development and should never be neglected by any public administrator. There are several cities around the world that have adopted the strategy under analysis as an urban planning tool, aiming to create more compact cities with a focus on active modes of transport and public transportation. In Brazil, Curitiba is often cited as an example of successful implementation of the principles of the strategy in question. Several other cities in Brazil also adopt the principles of TOD as a planning strategy, such as São Paulo and Goiânia. This dissertation seeks to answer the following question: is TOD capable of promoting development in cities? Using Hirschman's economic theories and the applicability of the strategy in municipalities in Brazil and around the world, the aim is to analyze its effectiveness in the municipality of Goiânia. Thus, the general objective is to analyze the strategy under discussion as a tool for urban planning in cities. As a specific objective, the study in question aims to analyze the experience of Brazilian cities regarding the strategy in question, focusing on the cities of Curitiba, São Paulo and, mainly, Goiânia. As a methodology, this study adopts a descriptive and qualitative approach. The deductive method is used, based on the literature review and the case study, to analyze existing theories and apply them to the context of TOD for urban development. This dissertation is structured into three main chapters